Recent investigations in the Puuc region of Yucatán - Rubenstein, Meghan (Archaeopress Pre-Columbian archaeology, 2017)
The authors assembled in this volume share a common research interest in the Puuc region of Mexico, a hilly landscape that stretches from the southern portion of the state of Yucatan into northern Campeche. As a collection, the papers demonstrate a myriad of approaches to understanding the history of the Puuc region, incorporating archaeological, architectural, epigraphic, and iconographic studies. The geographic scope is also broad. Many of the recent and ongoing archaeological projects in the eastern Puuc region and its periphery are represented, including Dzehkabtún, H'wasil, Kabah, Kiuic, Labná, Sayil, Uxmal, and Xcoch, as well as the Chocholá ceramic tradition from the western Puuc. This compilation offers an overview of the present state of research in the Puuc region while contributing new data, methodologies, and interpretations to the field of Mesoamerican studies.